Association between histologic grades and Ki67 score in breast cancer - Dr Shumaila Nawaz Khan Khan; Ghulam Haider; Kaneez Zainab Rabial; Saima Zahoor; Abdul Rehman; Aakash Ramchand; Munazza Anwer; Mehwish Jabeen (Liaquat Medical Research Journal)
Ki 67 is a key proliferative marker in breast cancer, often associated with tumor aggressiveness and grade. Despite its established role, the correlation between Ki 67 and histological grade remains inconsistent across studies. This study aimed to explore the association between Ki 67 expression and tumor grades in breast cancer patients. This was a cross-sectional study conducted at the Department of Medical Oncology, Jinnah Postgraduate Medical Centre (JPMC), Karachi, Pakistan over six months period (January 2024- June 2024). A sample of 78 breast cancer patients was included, divided into groups based on Ki 67 protein expression (Positive defined as >21% of positive cells). Histological grading was assessed by using the Elston-Ellis modification of Scarff-Bloom-Richardson grading system, while demographic and clinical data, including age, marital status, and BMI, were collected. High Ki-67 expression was observed predominantly in Grade 3 tumors (n=33, 91.7%) compared to Grade 2 (n=52, 66.7%) and Grade 1 (n=3, 50%) (p-value =0.008). No significant associations were found between Ki 67 and other variables, including tumor size, axillary lymph node involvement, and TNM stage. This study demonstrates a strong association between higher Ki 67 and advanced histological grades in breast cancer, suggesting that Ki 67 may serve as a valuable prognostic indicator. However, further research is needed to clarify its role in predicting clinical outcomes across diverse patient populations.